Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TS-TS) Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 4 Tarutung Tahun Pembelajaran 2023/2024 - Panggabean, Lima Udur; Napitupulu, Tianggur M; Telaumbanua, Eben H; Hulu, Adiani; Nababan, Damayanti (PT. Riset Press International, 2023)
The purpose of this study is to determine the positive and significant influence of the use of the Two Stay Two Stray (TS-TS) type cooperative learning model on the learning activity of PAK students of grade VIII SMP Negeri 4 Tarutung Learning Year 2023/2024. The research method used is quantitative research method. The population is all grade VIII students of SMP Negeri 4 Tarutung for the 2023/2024 learning year totaling 125 people and a sample of 62 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire of 34 items, namely 18 items for variable X and 16 items for variable Y. The results of data analysis showed that there was a positive and significant influence on the use of the Two Stay Two Stray (TS-TS) type cooperative learning model on the learning activity of PAK students of grade VIII SMP Negeri 4 Tarutung Learning Year 2023/2024: 1) Test analysis requirements: a) positive relationship test obtained rxy value = 0.624 > rtable(a=0,05,n=62) = 0,254. b) Test the relationship of significant obtained tcount values > ttabel(a=0,05,dk=n-2=60)= 2,000. 2) Test the influence: a) Test the regression equation, obtained regression equation. b) Regression coefficient of determination test (r2) = 38,9%. 3) Test the hypothesis using the F test obtained Fcalculate > Ftable=(a=0.05,dk numerator k=20,dk denominator=n-2=62-2=60) which is 38.16 > 1.39. Thus, Ha is accepted and H0 is rejected.